Neural correlates of motor imagery and observation in springboard diving - Pithan, J. M.; Stoll, O. (Conference: 14th European Congress of Sport Psychology Sport Psychology Theories and Applications for Performance, Health and Humanity 14-19 July 2015, 2015)
Motor imagery and mental practice are crucial elements in training and competition of springboard and platform divers. As the simulation theory (Jeannerod, 2001) posits, simulations of action such as motor imagery and motor observation share neural activation patterns with motor execution. A single-case comparison was performed to gain a first insight into neuronal activation patterns within motor imagery and observation, each from internal and external visual perspective. In accordance with the coaches the reverse two-and-a-half somersaults, tuck (305c) was used in this study. One internationally competing springboard diver (male, aged 27) was compared to one age-matched control participant (male, aged 27, internationally experienced judoka), and one youth springboard diver (female, aged 16). 32-Channel EEG was recorded for 40 trials of each condition (RCT). All trials were shown on a screen and introduced by baseline measurement and a preparation phase with condition specific symbols, which were then shown in imagery conditions or replaced by a video in observation conditions. Participants were instructed to imagine the dive as vividly as possible or to put themselves in the position of the recorded diver as well as possible. Event-related desynchronization (ERD) analysis was performed in alpha-frequency (8-12Hz). The youth athlete showed widespread ERD in all four conditions within the two seconds of preparation and the first two seconds of execution. The control participant showed more focused activation in form of ERD than the youth athlete and activation patterns comparable with the adult diver but with more central and frontal activation. The adult diver showed the most focused ERDs postcentral in all four conditions. The results are consistent with the neural efficiency hypothesis (Del Percio et al., 2008) which claims that neural activation patterns enlarge less topographically with level of expertise. These finding can be used for further investigation and psychological training in springboard diving.